Analisis Hotspot Pada PMS Gardu Induk 150 KV Rawadenok Depok Menggunakan Metode Thermovision - Abdul Multi; Hafizh Mubarok; Sugianto Sugianto (Institut Sains dan Teknologi Nasional, 2022)
Abstract Hotspot analysis at PMS Substation 150 kV Rawadenok Depok using the thermovision method was initiated based on hotspot events on Contact Finger phase S and Disconnecting Switch phase S. This analysis uses the Thermovisi Flir 400 tool as a means of checking high current temperatures that occur in Contact Finger phase S and Disconnecting Switches. The function of this thermovision is to measure the value of the ratio of the energy radiated by an object to the energy radiated by a black body at the same temperature and wave. Then measure the accuracy of Thermovisi starting from the value when checking, testing emissivity values, precision test values, accuracy values and repairs at hotspot points. From the results of the calculation of thermovision accuracy at Bay Cimanggis 1 & 2, it can be concluded that the temperature of the clamps and conductors shows that the conditions are still good. Where the RSM value of 27 samples is 0.4751, and has a coefficient variation (CV) of 0.1% and is categorized as good with a reference of no more than 2%, and has an accuracy value of 97.51%. Prior to the improvement of the hotspot points on Contact Finger it reached 115 oC and the DS Line S phase reached 103 oC after the temperature improvement returned to normal with Contact Finger reaching 36oC and the DS Line S phase reaching 31.2 oC. Keywords : PMS, Thermovisi, Hotspot, Emisivitas